Preparation method of ratio fluorescent nanoprobe for liquid / solid phase double visual detection of uric acid

Through the nanosystems of cobalt/silver/iron tri-doped boron quantum dots, uric acid oxidase and rhodamine B, the problem of liquid/solid phase detection of uric acid is solved in the existing technology, and the ratio fluorescence detection of uric acid is achieved and Dual visual inspection of liquid/solid phase, with efficient, fast and accurate detection capabilities.

CN119490968APending Publication Date: 2025-02-21QINGDAO UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411612278.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-21

Smart Images

  • Figure CN119490968A_ABST
    Figure CN119490968A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a ratiometric fluorescent nanoprobe for liquid / solid phase double visual detection of uric acid. Cobalt / silver / iron tri-doped boron quantum dots Co / Ag / Fe: BQDs are prepared, and a nano composite system is formed by the BQDs, urate oxidase UOx and rhodamine RhB. After uric acid is added, a cascade catalytic reaction is initiated, the uric acid is oxidized to generate hydrogen peroxide H2O2, the H2O2 activates the activity of Co / Ag / Fe: BQDs peroxidase, fluorescence quenching is caused, a hydroxyl free radical. OH is generated, and the. OH causes RhB fluorescence quenching. Due to the fact that fluorescence quenching of Co / Ag / Fe: BQDs and RhB in a system is caused by adding uric acid, the linear relation between the fluorescence peak intensity ratio of Co / Ag / Fe: BQDs and RhB in the system and the concentration of uric acid in the system is fitted, and the ratiometric fluorescence nanoprobe is obtained and used for ratiometric fluorescence detection of uric acid in a biological fluid sample and liquid / solid phase double visual detection of uric acid based on ratiometric fluorescence.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of ratio fluorescent probes, fluorescent visualization probes and nano-bioprobes, and specifically relates to a method for preparing a ratio fluorescent nano-probe for liquid / solid phase dual visualization detection of uric acid. The prepared probe is used for ratio fluorescent detection of uric acid in biological fluid samples, and liquid samples are placed in reagent bottles and dripped on solid substrates to achieve liquid / solid phase dual visualization detection of uric acid. Background Art

[0002] The chemical name of uric acid is 7,9-dihydro-2,6,8(3H)trione-1H-purine, and its chemical formula is C 5 H 4 N 4 O 3 , is the end product of purine metabolism and is a trioxypurine. The main product of healthy human urine is urea, which contains a small amount of uric acid. Drinking more water is conducive to the excretion of uric acid. When the uric acid concentration in human blood is greater than 7mg / dl, the body fluids become acidic. If uric acid in the body is not excreted in time or the uric acid excretion mechanism degenerates, excessive uric acid retention will occur, which will cause gout. Excessive fatigue or lack of rest can also cause the body's ability to metabolize uric acid to decrease, leading to the onset of gout. Therefore, convenient, fast, accurate and efficient detection of uric acid in the body is of great significance for daily care of human health, disease monitoring and clinical diagnosis and treatment.

[0003] Clinically, the main methods for checking uric acid include testing blood uric acid by venous blood sampling and testing uric acid in urine by standard 24-hour urine retention method. Patients with hyperuricemia generally take aerobic exercise, daily conditioning, medication, etc. for related treatment. Uric acid in serum or plasma is usually determined by phosphotungstic acid reduction colorimetry and enzyme catalysis. Phosphotungstic acid reduction colorimetry refers to the reduction of phosphotungstic acid by uric acid to blue tungsten blue in a protein-free alkaline environment, and colorimetric quantification is performed at an absorption wavelength of 660 nanometers. The enzyme catalysis method generally refers to the oxidation of uric acid to generate allantoin and hydrogen peroxide under the catalysis of urate oxidase. The latter reacts with the chromogen under the action of peroxidase to develop color, and then the colorimetric method is used for quantification.

[0004] At present, the detection methods of uric acid mainly include colorimetry, fluorescence, electrochemistry, photoelectrochemistry, photothermal, surface enhanced Raman scattering, paper chromatography, as well as sensors, chips, test kits, uric acid detectors, etc. In contrast, visual detection has significant advantages. It can intuitively reflect the concentration of uric acid in the system by observing the changes in different color types and color depths, making the detection more intuitive, convenient and quick. For example, Chen Guoqing and others prepared carbon dots using 3-aminophenylboronic acid and L-glutamine as raw materials. Uric acid and carbon dots formed a complex through electrostatic interaction, which led to the fluorescence quenching of carbon dots, so as to realize the visual detection of uric acid (Chen Guoqing; Li Xin; Wu Yamin; Ma Chaoqun; Li Lei; Zhu Chun; Gu Jiao; Gao Hui. National invention patent application number CN202311527113.2). Chen Haibin and others uniformly filled monodisperse microspheres with hydrogel prepolymer containing uric acid recognition monomers to form a hierarchical photonic crystal hydrogel. The response range of uric acid concentration corresponds to different colors to achieve visual detection of uric acid (Chen Haibin; Zhang Xinya; Shen Huifang. National invention patent application number CN202310186259.9). Zhu Hongni used gold nanoparticles as peroxidase nanozymes and 3,3',5,5'-tetramethylbenzidine as a color developer. Based on the peroxidase-like effect of gold nanoparticles and the change in color intensity, visual non-enzyme detection of uric acid content was achieved (Zhu Hongni. National invention patent application number CN202210880038.7).

[0005] Although previous papers, patents and related literature have reported various analytical methods and detection technologies for uric acid detection, there are few literature reports on the research work on the ratio fluorescence nanoprobe with liquid / solid phase dual visualization detection of uric acid and its experimental preparation and analytical application. The present invention discloses a nanosystem composed of three components: cobalt / silver / iron tri-doped boron quantum dots, uricase oxidase and rhodamine B. A cascade catalytic reaction occurs in the nanosystem triggered by uric acid, which eventually causes the fluorescence quenching response of cobalt / silver / iron tri-doped boron quantum dots and rhodamine B, and then develops into a ratio fluorescence nanoprobe. The probe is used for ratio fluorescence detection of uric acid in biological fluid samples, and for liquid / solid phase dual visualization detection of uric acid by placing the liquid sample in a reagent bottle and dripping it on a solid substrate. Summary of the invention

[0006] The purpose of the present invention is to develop a method for preparing a ratio fluorescent nanoprobe that is simple in design, convenient and efficient and can be used for liquid / solid phase dual visual detection of uric acid. The prepared probe is used for visual detection of uric acid in biological fluids and realizes liquid / solid phase dual visual detection of uric acid.

[0007] In order to achieve the above-mentioned object, the present invention relates to a ratiometric fluorescent nanoprobe for liquid / solid phase dual visualization detection of uric acid, and the preparation method thereof specifically comprises the following steps:

[0008] (1) Boron powder is used as a raw material to prepare a uniform dispersion of the boron powder in a solvent, and then aqueous solutions of cobalt nitrate, silver nitrate and ferric chloride are added in sequence under sufficient stirring to form a uniform mixed dispersion; the solvent used is dimethylformamide, nitrogen methyl pyrrolidone or ethylene glycol; the mass ratio of the three metal salts is adjusted to 5 / 1 / 1 to 1 / 1 / 5; the mass concentrations of the three metal salts and the boron powder in the uniform mixed dispersion are adjusted to 0.01 to 0.1 mg / ml and 0.1 to 1.0 mg / ml respectively;

[0009] (2) treating the mixed dispersion by probe ultrasound at 400 watts for 3 minutes, then pausing for 5 minutes, and maintaining the "ultrasound + pause" cycle for 1 to 3 hours; then treating the mixed dispersion by bath ultrasound at 40 kHz and 60° C. for 6 to 12 hours; then transferring the treated mixed dispersion into a micro autoclave, adding 2 to 5 drops of diluted polyethylene glycol PEG-400 as a surface stabilizer, and stirring under nitrogen atmosphere, magnetic stirring and 1 The reaction was continued at a temperature of 00 to 200° C. for 8 to 16 hours; after the reaction was completed, the product mixture was cooled to room temperature, centrifuged at a speed of 3500 rpm for 15 minutes to remove larger impurities, the upper clear liquid of the centrifuged mixture was absorbed, and centrifuged at a speed of 12000 rpm for 10 minutes; the obtained precipitate was repeatedly washed with ethanol and double distilled water to obtain the product, and the product was vacuum dried for 12 hours to obtain dry cobalt / silver / iron tri-doped boron quantum dots Co / Ag / Fe:BQDs;

[0010] (3) using ethanol and double distilled water as a mixed solvent to prepare a dispersion of Co / Ag / Fe:BQDs, and then adding appropriate amounts of urate oxidase UOx solution and rhodamine RhB solution in sequence under magnetic stirring to form a three-component nanocomposite system of "Co / Ag / Fe:BQDs+UOx+RhB" through intermolecular interaction and self-assembly; wherein the concentrations of Co / Ag / Fe:BQDs, UOx and RhB in the dispersion of the nanocomposite system are adjusted to 0.1-1.0 mg / ml, 0.05-0.1 equivalent / ml and 0.01-0.1 mg / ml, respectively;

[0011] (4) Adding an appropriate amount of uric acid to the above nanocomposite dispersion to form a homogeneous mixture under magnetic stirring, measuring the fluorescence emission spectrum of the homogeneous mixture using a fluorescence spectrometer, fitting the linear relationship between the maximum fluorescence peak intensity ratio of Co / Ag / Fe:BQDs and RhB and the uric acid concentration in the homogeneous mixture, and obtaining a ratio fluorescence nanoprobe for detecting uric acid based on "Co / Ag / Fe:BQDs+UOx+RhB"; wherein the linear detection range of uric acid concentration is 0.1 to 500 μmol / L, and the detection limit is 0. 01~0.1 μmol / L; within the uric acid concentration range of 0.1~500 μmol / L, 16~20 concentration gradients are selected to prepare a series of nanoprobe system dispersions containing specific uric acid concentrations, and then each dispersion is placed in a reagent bottle or dripped on a filter paper strip, and a digital camera is used to photograph the color of each dispersion in the reagent bottle or on the filter paper strip under ultraviolet light excitation; based on the one-to-one correspondence between the observed fluorescent color of each dispersion and the corresponding specific uric acid concentration, a liquid / solid phase dual visualization colorimetric card for detecting uric acid concentration is established.

[0012] The effect of the present invention is to disclose a method for preparing a ratio fluorescent nanoprobe for liquid / solid phase dual visualization detection of uric acid. First, cobalt / silver / iron tri-doped boron quantum dots Co / Ag / Fe:BQDs were prepared by ultrasound-assisted solvothermal reaction, and then the three-component nanocomposite system of "Co / Ag / Fe:BQDs+UOx+RhB" was formed by intermolecular interaction and self-assembly with urate oxidase UOx and rhodamine RhB. Uric acid was added to the dispersion of the system to initiate a cascade catalytic reaction, and UOx oxidized uric acid into urea and hydrogen peroxide H 2 O 2 , while H 2 O 2 The peroxidase-like activity of Co / Ag / Fe:BQDs was activated, and the fluorescence quenching response of Co / Ag / Fe:BQDs and the generation of hydroxyl radicals ·OH were caused at the same time; and ·OH also caused the fluorescence quenching response of RhB. Based on this, the addition of uric acid led to the fluorescence quenching response of Co / Ag / Fe:BQDs and RhB in the nanocomposite system. The linear relationship between the maximum fluorescence peak intensity ratio of Co / Ag / Fe:BQDs and RhB and the uric acid concentration in the system was fitted, and a ratio fluorescence nanoprobe for detecting uric acid was obtained. The probe was applied to the ratio fluorescence detection of uric acid in biological fluid samples. The liquid sample containing uric acid was placed in a reagent bottle and dripped on a solid substrate, and the liquid / solid dual visualization detection of uric acid was realized based on the ratio fluorescence probe. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1The present invention is a method for preparing a ratiometric fluorescent nanoprobe for liquid / solid phase dual visualization detection of uric acid and a schematic diagram of the principle of its visualization detection of uric acid. DETAILED DESCRIPTION

[0014] The present invention will be described in detail below with reference to the accompanying drawings and through specific embodiments.

[0015] Example 1

[0016] The present embodiment relates to a method for preparing a ratiometric fluorescent nanoprobe for liquid / solid phase dual visual detection of uric acid and the principle of visual detection of uric acid as follows: Figure 1 As shown, the specific preparation steps are as follows:

[0017] Add 40 mg of boron powder to 40 ml of nitrogen methyl pyrrolidone and stir thoroughly to form a uniform dispersion. Under stirring, add 10 mg of cobalt nitrate, 2 mg of silver nitrate and 2 mg of ferric chloride in water in turn to form a mixed dispersion. Treat the mixed dispersion with probe ultrasound, ultrasonicate at 400 watts for 3 minutes and then pause for 5 minutes, and maintain the "ultrasound + pause" cycle for 1 hour. Then use bath ultrasound for 8 hours at 40 kHz and 60°C, and then transfer the treated mixed dispersion to a micro-autoclave. Add 2 drops of diluted polyethylene glycol PEG-400 (1 ml of double distilled water diluted with 0.2 ml of PEG-400) as a surface stabilizer and stir at N 2 The reaction was carried out under protection, magnetic stirring and 120 ° C for 8 hours. After the reaction, the product mixture was cooled to room temperature, centrifuged at 3500 rpm for 15 minutes to remove larger impurities, and the upper layer of the centrifuged mixture was taken and centrifuged at 12000 rpm for 10 minutes. The obtained precipitate was washed 3 times with ethanol and double distilled water respectively, and then transferred to vacuum drying for 12 hours, and finally the pure and dry cobalt / silver / iron tri-doped boron quantum dots Co / Ag / Fe:BQDs were obtained.

[0018] A Co / Ag / Fe:BQDs dispersion was prepared by using ethanol and double distilled water in a volume ratio of 1:2 as a mixed solvent, and a urate oxidase UOx solution and a rhodamine RhB solution were added in sequence under stirring to form a "Co / Ag / Fe:BQDs+UOx+RhB" three-component nanocomposite system. The concentrations of Co / Ag / Fe:BQDs, UOx and RhB in the dispersion of the system were 0.2 mg / ml, 0.05 equivalents / ml and 0.02 mg / ml, respectively. Uric acid was added to the dispersion of the system to form a homogeneous mixture under stirring, and the fluorescence emission spectrum of the homogeneous mixture was measured. The linear relationship between the maximum fluorescence peak intensity ratio of Co / Ag / Fe:BQDs and RhB and the uric acid concentration in the homogeneous mixture was fitted to obtain a ratio fluorescence nanoprobe for detecting uric acid. Among them, the linear detection range of uric acid concentration is 0.5-100 micromol / L, and the detection limit is 0.02 micromol / L. Within the uric acid concentration range of 0.1-500 micromol / L, 16 concentration gradients were selected to prepare a series of nanoprobe dispersions containing specific uric acid concentrations. Each dispersion was then placed in a reagent bottle or dripped onto a filter paper strip, and a digital camera was used to photograph the color of each dispersion in the reagent bottle or on the filter paper strip under ultraviolet light excitation. Based on the one-to-one correspondence between the observed fluorescence color of each dispersion and the corresponding specific uric acid concentration, a liquid / solid phase dual visualization colorimetric card for detecting uric acid concentration was established.

[0019] Example 2

[0020] The present embodiment relates to a method for preparing a ratiometric fluorescent nanoprobe for liquid / solid phase dual visual detection of uric acid and the principle of visual detection of uric acid as follows: Figure 1 As shown, the specific preparation steps are as follows:

[0021] Add 50 mg of boron powder to 50 ml of dimethylformamide and stir thoroughly to form a uniform dispersion. Add 5 mg of cobalt nitrate, 5 mg of silver nitrate and 5 mg of ferric chloride in water in turn while stirring to form a mixed dispersion. Treat the mixed dispersion with probe ultrasound, ultrasonicate at 400 watts for 3 minutes and then pause for 5 minutes, and maintain the "ultrasound + pause" cycle for 2 hours. Then use a bath ultrasound treatment at 40 kHz and 60°C for 10 hours, and then transfer the treated mixed dispersion to a micro-autoclave. Add 3 drops of diluted polyethylene glycol PEG-400 (1 ml of double distilled water diluted with 0.2 ml of PEG-400) as a surface stabilizer and place it in N 2The reaction was carried out under protection, magnetic stirring and 150 ° C for 10 hours. After the reaction, the product mixture was cooled to room temperature, centrifuged at 3500 rpm for 15 minutes to remove larger impurities, and the upper layer of the centrifuged mixture was taken and centrifuged at 12000 rpm for 10 minutes. The obtained precipitate was washed 3 times with ethanol and double distilled water respectively, and then transferred to vacuum drying for 12 hours, and finally the pure and dry cobalt / silver / iron tri-doped boron quantum dots Co / Ag / Fe:BQDs were obtained.

[0022] A Co / Ag / Fe:BQDs dispersion was prepared by using ethanol and double distilled water in a volume ratio of 1:2 as a mixed solvent, and a urate oxidase UOx solution and a rhodamine RhB solution were added in sequence under stirring to form a "Co / Ag / Fe:BQDs+UOx+RhB" three-component nanocomposite system. The concentrations of Co / Ag / Fe:BQDs, UOx and RhB in the dispersion of the system were 0.4 mg / ml, 0.06 equivalents / ml and 0.04 mg / ml, respectively. Uric acid was added to the dispersion of the system to form a homogeneous mixture under stirring, and the fluorescence emission spectrum of the homogeneous mixture was measured. The linear relationship between the maximum fluorescence peak intensity ratio of Co / Ag / Fe:BQDs and RhB and the uric acid concentration in the homogeneous mixture was fitted to obtain a ratio fluorescence nanoprobe for detecting uric acid. Among them, the linear detection range of uric acid concentration is 0.2-200 micromol / L, and the detection limit is 0.05 micromol / L. Within the uric acid concentration range of 0.1-500 micromol / L, 18 concentration gradients were selected to prepare a series of nanoprobe dispersions containing specific uric acid concentrations. Each dispersion was then placed in a reagent bottle or dripped onto a filter paper strip, and a digital camera was used to photograph the color of each dispersion in the reagent bottle or on the filter paper strip under ultraviolet light excitation. Based on the one-to-one correspondence between the observed fluorescence color of each dispersion and the corresponding specific uric acid concentration, a colorimetric card for liquid / solid phase dual visualization detection of uric acid concentration was established.

[0023] Example 3

[0024] The present embodiment relates to a method for preparing a ratiometric fluorescent nanoprobe for liquid / solid phase dual visual detection of uric acid and the principle of visual detection of uric acid as follows: Figure 1 As shown, the specific preparation steps are as follows:

[0025] Add 60 mg of boron powder to 60 ml of ethylene glycol and stir thoroughly to form a uniform dispersion. Add 2 mg of cobalt nitrate, 2 mg of silver nitrate and 10 mg of ferric chloride in water in turn while stirring to form a mixed dispersion. Treat the mixed dispersion with probe ultrasound, ultrasonicate at 400 watts for 3 minutes and then pause for 5 minutes, and maintain the "ultrasound + pause" cycle for 3 hours. Then use a bath ultrasound treatment at 40 kHz and 60°C for 12 hours, and then transfer the treated mixed dispersion to a micro-autoclave. Add 4 drops of diluted polyethylene glycol PEG-400 (1 ml of double distilled water diluted with 0.2 ml of PEG-400) as a surface stabilizer and place it in N 2 The reaction was carried out under protection, magnetic stirring and 180 ° C for 12 hours. After the reaction, the product mixture was cooled to room temperature, centrifuged at 3500 rpm for 15 minutes to remove larger impurities, and the upper layer of the centrifuged mixture was taken and centrifuged at 12000 rpm for 10 minutes. The obtained precipitate was washed 3 times with ethanol and double distilled water respectively, and then transferred to vacuum drying for 12 hours, and finally the pure and dry cobalt / silver / iron tri-doped boron quantum dots Co / Ag / Fe:BQDs were obtained.

[0026] A Co / Ag / Fe:BQDs dispersion was prepared by using ethanol and double distilled water in a volume ratio of 1:2 as a mixed solvent, and a urate oxidase UOx solution and a rhodamine RhB solution were added in sequence under stirring to form a "Co / Ag / Fe:BQDs+UOx+RhB" three-component nanocomposite system. The concentrations of Co / Ag / Fe:BQDs, UOx and RhB in the dispersion of the system were 0.6 mg / ml, 0.08 equivalents / ml and 0.06 mg / ml, respectively. Uric acid was added to the dispersion of the system to form a homogeneous mixture under stirring, and the fluorescence emission spectrum of the homogeneous mixture was measured. The linear relationship between the maximum fluorescence peak intensity ratio of Co / Ag / Fe:BQDs and RhB and the uric acid concentration in the homogeneous mixture was fitted to obtain a ratio fluorescence nanoprobe for detecting uric acid. Among them, the linear detection range of uric acid concentration is 0.2-500 micromol / L, and the detection limit is 0.08 micromol / L. Within the uric acid concentration range of 0.1-500 micromol / L, 20 concentration gradients were selected to prepare a series of nanoprobe dispersions containing specific uric acid concentrations. Each dispersion was then placed in a reagent bottle or dripped onto a filter paper strip, and a digital camera was used to photograph the color of each dispersion in the reagent bottle or on the filter paper strip under ultraviolet light excitation. Based on the one-to-one correspondence between the observed fluorescence color of each dispersion and the corresponding specific uric acid concentration, a liquid / solid phase dual visualization colorimetric card for detecting uric acid concentration was established.

[0027] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a ratiometric fluorescent nanoprobe for liquid / solid phase dual visualization detection of uric acid, characterized in that: The preparation method specifically comprises the following steps: (1) Boron powder is used as a raw material to prepare a uniform dispersion of the boron powder in a solvent, and then aqueous solutions of cobalt nitrate, silver nitrate and ferric chloride are added in sequence under sufficient stirring to form a uniform mixed dispersion; the solvent used is dimethylformamide, nitrogen methyl pyrrolidone or ethylene glycol; the mass ratio of the three metal salts is adjusted to 5 / 1 / 1 to 1 / 1 / 5; the mass concentrations of the three metal salts and the boron powder in the uniform mixed dispersion are adjusted to 0.01 to 0.1 mg / ml and 0.1 to 1.0 mg / ml respectively; (2) treating the mixed dispersion by probe ultrasound at 400 watts for 3 minutes, then pausing for 5 minutes, and maintaining the "ultrasound + pause" cycle for 1 to 3 hours; then treating the mixed dispersion by bath ultrasound at 40 kHz and 60°C for 6 to 12 hours; then transferring the treated mixed dispersion into a micro autoclave, adding 2 to 5 drops of diluted polyethylene glycol PEG-400 as a surface stabilizer, and stirring under nitrogen atmosphere, magnetic stirring and 1 The reaction was continued at a temperature of 00 to 200° C. for 8 to 16 hours; after the reaction was completed, the product mixture was cooled to room temperature, centrifuged at a speed of 3500 rpm for 15 minutes to remove larger impurities, the upper clear liquid of the centrifuged mixture was absorbed, and centrifuged at a speed of 12000 rpm for 10 minutes; the obtained precipitate was repeatedly washed with ethanol and double distilled water to obtain the product, and the product was vacuum dried for 12 hours to obtain dry cobalt / silver / iron tri-doped boron quantum dots Co / Ag / Fe:BQDs; (3) using ethanol and double distilled water as a mixed solvent to prepare a dispersion of Co / Ag / Fe:BQDs, and then adding appropriate amounts of urate oxidase UOx solution and rhodamine RhB solution in sequence under magnetic stirring to form a three-component nanocomposite system of "Co / Ag / Fe:BQDs+UOx+RhB" through intermolecular interaction and self-assembly; wherein the concentrations of Co / Ag / Fe:BQDs, UOx and RhB in the dispersion of the nanocomposite system are adjusted to 0.1-1.0 mg / ml, 0.05-0.1 equivalent / ml and 0.01-0.1 mg / ml, respectively; (4) Adding an appropriate amount of uric acid to the above nanocomposite dispersion to form a homogeneous mixture under magnetic stirring, measuring the fluorescence emission spectrum of the homogeneous mixture using a fluorescence spectrometer, fitting the linear relationship between the maximum fluorescence peak intensity ratio of Co / Ag / Fe:BQDs and RhB and the uric acid concentration in the homogeneous mixture, and obtaining a ratio fluorescence nanoprobe for detecting uric acid based on "Co / Ag / Fe:BQDs+UOx+RhB"; wherein the linear detection range of uric acid concentration is 0.1 to 500 μmol / L, and the detection limit is 0. 01~0.1 μmol / L; within the uric acid concentration range of 0.1~500 μmol / L, 16~20 concentration gradients are selected to prepare a series of nanoprobe system dispersions containing specific uric acid concentrations, and then each dispersion is placed in a reagent bottle or dripped on a filter paper strip, and a digital camera is used to photograph the color of each dispersion in the reagent bottle or on the filter paper strip under ultraviolet light excitation; based on the one-to-one correspondence between the observed fluorescent color of each dispersion and the corresponding specific uric acid concentration, a liquid / solid phase dual visualization colorimetric card for detecting uric acid concentration is established.

Citation Information

Patent Citations

  • A Visualized Uric Acid Detection Method Based on Nanomaterials

    CN114935572A

  • Photonic crystal hydrogel for visual uric acid detection and preparation method and application thereof

    CN116626025A

  • Method for visually detecting uric acid based on fluorescent carbon dots

    CN117420111A